Dietary Pattern and Its Impact on Nutritional Status of Adolescent Girls among Chepang Community in Raksirang Rural-Municipality of Makawanpur District - Uprety, Vivek; Pandey, Bipindra; Sigdel, Manoj; Bhandari, Keshab Raj; Neupane, Sunil; Karki, Kshitiz (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Adolescence is a period of transition between childhood and adulthood. An adolescent is defined as individuals in the 10-19year age group. The health and nutritional status of adolescent girls affects their health and their survival in future. Adolescents, particularly girls, are increasingly conscious of their body which leads to low intake of food rich with nutrients. Teenage girls may excessively restrict their energy intake, out of a desire to be thin, which has a serious threat on their nutritional status. Methods: Descriptive cross sectional study design was applied in ward number 5 of Raksirangrural municipality of Makawanpur district usingsemi-structured questionnaire and all adolescent girls (127) of aged 10-19 years were involved as the respondents of the study. The study duration was 7th June to 25th December 2017. The data was entered and analyzed with the help of software SPSS version 16.0. Results: The prevalence of underweight was found to be 27.6%. Study shows the participants consume protective fruits and vegetables group and other fruits and vegetables group in less quantity as comparison to other food groups. Though most of the participants were literate, knowledge on nutrition about 8% had adequate knowledge and 91% had poor knowledge. Conclusions: Nutritional status of adolescent girls of Raksirangrural municipality is found to be poor. The research recommends improving nutritional status and feeding habits especially intake of wheat, meat and yellow fruits focusing on adolescent girls.